A systematic review and Meta-analysis of erosion occurrences on forest roads - Muhamad Nazrain Buniran; Mohd Hasmadi Ismail; Pakhriazad Hassan Zaki; Paiman Bawon; Rahmawaty; Seca Gandaseca (Talenta Publisher, 2026)
Forest roads are essential in forested regions, supporting forestry operations, timber extraction, afforestation, log transportation to mills, recreation, and wildlife management. Nonetheless, forest roads are a major source of soil erosion and sedimentation in stream waters. They contribute to sedimentation through soil erosion on elements like the running surface, roadside slopes, and side ditches. On these routes, soil erosion primarily occurs due to rainfall-driven runoff and its duration. This study employs a systematic review, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), to compile data and examine findings on forest road erosion. The review aligns with the objectives of identifying factors that influence soil erosion on forest roads and skid trails, and developing techniques to control erosion, minimise its impact, and prevent its occurrence. Methods such as planting vegetation on roadside slopes have demonstrated effectiveness in mitigating erosion and reducing its severity and extent. It is advisable for future research to explore various soil erosion control techniques to deepen understanding and improve measures to reduce soil erosion on forest roads